Piperine Suppresses Pyroptosis and Interleukin-1β Release upon ATP Triggering and Bacterial Infection - Liang, Yi-Dan; Bai, Wen-Jing; Li, Chen-Guang; Xu, Li-Hui; Wei, Hong-Xia; Pan, Hao; He, Xian-Hui; Ouyang, Dong-Yun (Frontiers in Pharmacology, 2016)
Piperine is a phytochemical present in black pepper (Piper nigrum Linn) and other related herbs, possessing a wide array of pharmacological activities including anti-inflammatory effects. Previously, we demonstrated that piperine has therapeutic effects on bacterial sepsis in mice, but the underlying mechanism has not been fully elucidated. In this study, we aimed to investigate the influences of piperine on pyroptosis in murine macrophages. The results showed that piperine dose-dependently inhibited ATP-induced pyroptosis, thereby suppressing interleukin-1β (IL-1β) or high mobility group box-1 protein (HMGB1) release in LPS-primed bone marrow-derived macrophages (BMDMs) and J774A.1 cells. Accompanying this, ATP-induced AMP-activated protein kinase (AMPK) activation was greatly suppressed by piperine, whereas AMPK agonist metformin counteracted piperine’s inhibitory effects on pyroptosis. Moreover, piperine administration greatly reduced both peritoneal and serum IL-1β levels in the mouse model intraperitoneally infected with Escherichia coli, suggestive of suppressing systemic inflammation and pyroptosis. Our data indicated that piperine could protect macrophages from pyroptosis and reduced IL-1β and HMGB1 release by suppressing ATP-induced AMPK activation, suggesting that piperine may become a potential therapeutic agent against bacterial sepsis.